2012
DOI: 10.1128/jcm.05715-11
|View full text |Cite
|
Sign up to set email alerts
|

Use of Illumina Deep Sequencing Technology To Differentiate Hepatitis C Virus Variants

Abstract: Hepatitis C virus (HCV) is a positive-strand enveloped RNA virus that shows diverse viral populations even in one individual. Though Sanger sequencing has been used to determine viral sequences, deep sequencing technologies are much faster and can perform large-scale sequencing. We demonstrate the successful use of Illumina deep sequencing technology and subsequent analyses to determine the genetic variants and amino acid substitutions in both treatment-naïve (patient 1) and treatmentexperienced (patient 7) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…This method provides a good idea of the major sequences present, but unfortunately it cannot detect minor variants that are present at a frequency below 20%-25% [106] . With the development of deep sequencing technologies, detection of drug-resistant variants became more sensitive allowing the identification of variants present at very low frequencies (about 0.1%-1%) [107][108][109] . For HCV, the deep sequencing method was first used to detect emergence of NS3 mutants.…”
Section: Next Generation Sequencing In Hcv Quasispecies Analysismentioning
confidence: 99%
“…This method provides a good idea of the major sequences present, but unfortunately it cannot detect minor variants that are present at a frequency below 20%-25% [106] . With the development of deep sequencing technologies, detection of drug-resistant variants became more sensitive allowing the identification of variants present at very low frequencies (about 0.1%-1%) [107][108][109] . For HCV, the deep sequencing method was first used to detect emergence of NS3 mutants.…”
Section: Next Generation Sequencing In Hcv Quasispecies Analysismentioning
confidence: 99%
“…Recent reports have described the advantages of ultradeep sequencing technology, including faster processing and large-scale sequencing, in addition to providing a better understanding of the dynamics of variants in HCV quasispecies (8)(9)(10)(11). However, it is not clear at this stage whether such technology is useful for the prediction of the emergence of telaprevir-resistant variants during or after the administration of triple therapy.…”
mentioning
confidence: 99%
“…The method provides a composite of the major sequences present but is limited in the detection of minor viral mutant subpopulations that present at Ͻ20% to 25% (7). With the development of allele-specific PCR, single-genome sequencing, and deep-sequencing technologies, the detection of drug-resistant variants became more sensitive with the current assay cutoff at about 0.1% to 1% (3,6,9). Further improvement of the assay sensitivity is constrained by uniform amplification of viral quasispecies and background noise from mutations generated during PCR amplification and sequencing.…”
mentioning
confidence: 99%
“…Further improvement of the assay sensitivity is constrained by uniform amplification of viral quasispecies and background noise from mutations generated during PCR amplification and sequencing. Several recent studies clearly demonstrated the utility of deep sequencing and other sensitive technologies to detect HCV quasispecies (3,6,9). The deep-sequencing method was first used to detect the emergence of NS3 mutants in an elegant infectious model of HCV using human hepatocyte chimeric mice.…”
mentioning
confidence: 99%